2010
DOI: 10.4315/0362-028x-73.2.344
|View full text |Cite
|
Sign up to set email alerts
|

Four-Year Surveillance for Ochratoxin A and Fumonisins in Retail Foods in Japan

Abstract: Between 2004 and 2007 we examined foods from Japanese retail shops for contamination with ochratoxin A (OTA) and fumonisins B(1), B(2), and B(3). A total of 1,358 samples of 27 different products were examined for OTA, and 831 samples of 16 different products were examined for fumonisins. The limits of quantification ranged from 0.01 to 0.5 microg/kg for OTA and 2 to 10 microg/kg for the fumonisins. OTA was detected in amounts higher than limits of quantification in wheat flour, pasta, oatmeal, rye, buckwheat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 34 publications
2
27
0
2
Order By: Relevance
“…OTA is found in grains and many other kinds of foodstuffs (Bayman and Baker 2006; Clark and Snedeker 2006); these include cocoa and cocoa products (reviewed by Codex Alimentarius Commission 2007, 2008; Tabata et al 2008; Chung et al 2009; Aoyama et al 2010; Brera et al 2011; Jayeola et al 2011; Nwagu and Ire 2011; Turcotte and Scott 2011; Copetti et al 2012a, 2013; Mounjouenpou et al 2012). The European Commission (EC) has stated that it does not appear necessary to set a maximum level for OTA in cocoa and cocoa products (European Commission 2010).…”
Section: Introductionmentioning
confidence: 99%
“…OTA is found in grains and many other kinds of foodstuffs (Bayman and Baker 2006; Clark and Snedeker 2006); these include cocoa and cocoa products (reviewed by Codex Alimentarius Commission 2007, 2008; Tabata et al 2008; Chung et al 2009; Aoyama et al 2010; Brera et al 2011; Jayeola et al 2011; Nwagu and Ire 2011; Turcotte and Scott 2011; Copetti et al 2012a, 2013; Mounjouenpou et al 2012). The European Commission (EC) has stated that it does not appear necessary to set a maximum level for OTA in cocoa and cocoa products (European Commission 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There is extensive documentation of OTA as a contaminant of coffee, green and roasted coffee beans having been analyzed by many Authors (Aoyama et al, 2010;Batista et al, 2009;Bresch, Urbanek, & Hell, 2000;Coronel, Marin, Cano, Ramos, & Sanchis, 2011;Jørgensen, 1998;Lombaert et al, 2002;Patel, Hazel, Winterton, & Gleadle, 1997;Quintana Guzmán, Antillón Guerrero, & Chaves, 2007;Ramesh & Vasanthi, 2005;Studer-Rohr, Dietrich, Schlatter, & Schlatter, 1995;Terada, Tsubouchi, Yamamoto, Hisada, & Sakabe, 1986;Urbano, Taniwaki, de, Leitao, & Vicentini, 2001;Van der Stegen et al, 1997). The fate of OTA during roasting and decaffeination processes has also been investigated (Blanc, Pittet, Muñoz-Box, & Viani, 1998;La Pera et al, 2008;Micco, Grossi, Miraglia, & Brera, 1989;Nehad, Farag, Kawther, Abdel-Samed, & Naguib, 2005;Romani, Pinnavaia, & Dalla Rosa, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, Aoyama et al (2010) found OTA in 90% of 63 samples analyzed in the 2004/07 period, the levels ranging from 0.1 to 4.23 mg/kg; Kawamura (2005) observed the presence of OTA in 12 samples, the levels ranging from 0.11 to 4.41 mg/kg; and, more recently, Tabata et al (2008) detected the toxin in 5 out of 7 soluble coffee samples, at levels of 0.16e1.1 mg/kg. In Brazil, Leoni, Valente Soares, and Oliveira (2000) found OTA in 16 instant coffees at levels ranging from 0.5 to 5.1 mg/kg; Prado et al (2000) observed OTA occurrence at levels between 0.31 and 1.78 mg/kg in 8 out 10 analyzed samples; and de Almeida et al (2007) found OTA in 81 samples out of 82, (98.8%) at levels ranging from 0.17 to 6.29 ng/g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Segundo Shephard et al (2011), a contaminação em milho continua sendo um problema global, entretanto as fumonisinas são encontradas também em outros alimentos como trigo (KUSHIRO et al, 2009;MONBALIU et al, 2010), mandioca (MANJULA et al, 2009), uvas e derivados como vinho (MOGENSEN et al, 2010), cerveja (AOYAMA et al, 2010), e aspargos (WAŚKIEWICZ et al, 2010).…”
Section: Ocorrência Em Alimentos Destinados Ao Consumo Humanounclassified